Solve 7b plz
(Transformation of trigonometric formulae )
#salute u if u solved it
Attachments:
![](https://hi-static.z-dn.net/files/d00/789070eb7740305240c2467f27f31f2a.jpg)
Answers
Answered by
11
Solution :-
Given to prove :-
Now multiply both numerator and denominator by 2 .
Now as
Sin(a + b) - Sin(a - b) = 2.Cos(a).Sin(b)
Cos(a - b) - Cos(a + b) = 2.Sin(a).Sin(b)
Cos(a - b) + Cos(a + b) = 2.Cos(a).Cos(b)
So our expression became :-
Now as we have
By applying it :-
Now
As LHS = RHS
Hence Proved
Similar questions